Analysis of Antibiotic Resistance Genes, Environmental Factors, and Microbial Community From Aquaculture Farms in Five Provinces, China - Cheng, Xu; Lu, Yitong; Song, Yanzhen; Zhang, Ruifang; ShangGuan, Xinyan; Xu, Hongzhou; Liu, Chengrong; Liu, Haixia (Frontiers in Microbiology, 2021)
The excessive use of antibiotics speeds up the dissemination and aggregation of antibiotic resistant genes (ARGs) in the environment. The ARGs have been regarded as a contaminant of serious environmental threats to the world. With the antibiotics widely used to prevent some diseases in aquatic farms, there is universal concern about the environmental risk of ARGs in the aquaculture environment. In this study, we conducted a survey to evaluate the abundance and distributions of 11 antibiotic-resistant genes, bacterial community and environmental factors in sediment samples of the aquatic farms from Anhui (AP1, AP2, AP3), Fujian (FP1, FP2, FP3) , Guangxi (GP1, GP2, GP3), Hainan(HP1, HP2, HP3) and Shaanxi(SP1, SP2, SP3) in China, respectively. Results showed that the relative abundance of total ARGs was higher in AP2, AP3, FP3, HP1, HP2 and HP3, and lower in GP1, GP2, SP1, SP2 and SP3. The sul1 and tetW genes had the highest abundance of all sediments. The class 1 integron (intl1) was detected in all samples, and Pearson correlation analysis showed that the intl1 has positivity correlation with the sul1, sul2, sul3, blaOXA, qnrS and tetM, tetQ and tetW gene. Correlation analysis of the bacterial community diversity and environmental factors showed that the Ca2+ concentration had negative correlation with the bacterial community richness and diversity in these samples. In the identified bacterial community, Proteobacteria, Firmicutes, Chloroflexi and Bacteroidota were the predominant phyla in these samples. Redundancy analysis showed that environmental factors (TN, TP, Cl- and Ca2+) have positive correlation with the bacterial community (AP1, GP1, GP2, GP3, SP1, SP2 and SP3), and the abundance of ARGs (sul1, tetW, qnrS and intl1) have positive correlation with the bacterial community (AP2, AP3, HP1, HP2 and HP3). Based on Network analysis, the ARGs has stronger co-occurrence with bacterial taxa from the phyla of Chlorflxi, Euryarchaeota, Firmicutes, Halobacterota and Proteobacteria. In conclusion, this study provides a reference to understanding the environmental risk associated with aquaculture activity in China.